Herbal medicine and its impact on the gut microbiota in colorectal cancer - Bu, Fan; Tu, Yifeng; Wan, Ziang; Tu, Shiliang (Frontiers in Cellular and Infection Microbiology, 2023)
It is well-established that there are trillions of gut microbiota (GM) in the human gut. GM and its metabolites can reportedly cause cancer by causing abnormal immune responses. With the development of sequencing technology and the application of germ-free models in recent years, significant inroads have been achieved in research on GM and microbiota-related metabolites. Accordingly, the role and mechanism of GM in colorectal cancer (CRC) development have been gradually revealed. Traditional Chinese medicine (TCM) represents an important source of natural medicines and herbal products, with huge potential as anti-CRC agents. The potential application of TCM to target gut microbes for the treatment of colorectal cancer represents an exciting area of investigation.